AN INTERACTION ANALYSIS AND ASSESSMENT OF RISK PERCEPTION, EQUITY INVESTMENT AND FINANCIAL INFORMATION AWARENESS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The Investment decision of investors is subjective  considering their dependence on various factors  such as socio-demographic variables, risk  perception, objectives, and financial information  awareness. Behavioral finance molds the  traditional definition of risk which implies  deviation from actual return with the perception  towards the risk which tends to vary from one  individual to another. Risk perception plays  an important role in determining investment  choice. The study attempts to identify the  prominent factors having impact on the risk  perception of individual investors of Sikkim  with the help of Factor Analysis. Primary data  consisting of 250 individuals were collected  by self-survey method. There are four factors  influencing the risk perception namely, Risk  Opportunist, Overconfident Risk Bearer,  Unrealistic Anticipator, and Cognizant Pursuer.  Binary logistic regression further enabled to  understand their impact on the investment  preference towards the equity shares. The  study revealed a significant and positive  relationship between risk perception and  financial information awareness.
Keywords: Risk Perception; Financial Information Awareness; Equity Shares; Binary Logistic Regression